Intergenerational solidarity and subjective economic vulnerability among older adults in Indonesia - Riani, Novya Zulva; Idris, Idris; Yeniwati, Yeniwati (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2026)
This study examines the influence of intergenerational relationships on the subjective economic vulnerability of older adults in Indonesia, with particular emphasis on reciprocal motives and bequest intentions within the framework of intergenerational solidarity. Using data from the fifth wave of the Indonesia Family Life Survey (IFLS-5) conducted in 2014, comprising 6,246 respondents aged 60 and above, the study estimates two forms of subjective vulnerability—self-assessed economic vulnerability and perceived economic vulnerability—using a bivariate probit regression model to address potential endogeneity between co-residence with adult children, health status, bequest motives, and vulnerability among older adults. The findings indicate that bequest motives significantly increase the likelihood of co-residing with adult children, reflecting reciprocal exchange mechanisms within multigenerational households. Physical and psychological health emerge as the strongest determinants of subjective vulnerability among older adults. This study makes an important empirical contribution by introducing an integrated model that links bequest motives, intergenerational solidarity, and subjective vulnerability within the context of a developing country. Overall, the results underscore the need for stronger synergy between family-based support and formal social protection systems to mitigate vulnerability risks among older adults in an era of population ageing.